Potential Bone to Implant Contact Area of Short Versus Standard Implants: An In Vitro Micro–Computed Tomography Analysis. Issue 1 (February 2016) - Quaranta, Alessandro; D'Isidoro, Orlando; Bambini, Fabrizio; Putignano, Angelo
Abstract : Aim: To compare the available potential bone-implant contact (PBIC) area of standard and short dental implants by micro–computed tomography (μCT) assessment. Methods: Three short implants with different diameters (4.5 × 6 mm, 4.1 × 7 mm, and 4.1 × 6 mm) and 2 standard implants (3.5 × 10 mm and 3.3 × 9 mm) with diverse design and surface features were scanned with μCT. Cross-sectional images were obtained. Image data were manually processed to find the plane that corresponds to the most coronal contact point between the crestal bone and implant. The available PBIC was calculated for each sample. Later on, the cross-sectional slices were processed by a 3-dimensional (3D) software, and 3D images of each sample were used for descriptive analysis and display the microtopography and macrotopography. Results: The wide-diameter short implant (4.5 × 6 mm) showed the higher PBIC (210.89 mm 2 ) value followed by the standard (178.07 mm 2 and 185.37 mm 2 ) and short implants (130.70 mm 2 and 110.70 mm 2 ). Conclusions: Wide-diameter short implants show a surface area comparable with standard implants. Micro-CT analysis is a promising technique to evaluate surface area in dental implants with different macrodesign, microdesign, and surface features.